Pemanfaatan Rambut Jagung (Zea mays L.) Menjadi Teh Herbal “KoNsilk” kepada Kader Puskesmas Perumnas 2 Kota Pontianak: Utilization of Corn Silk (Zea mays L.) Into "KoNsilk" Herbal Tea for Cadres of Public Health Center 2 Pontianak City - Bambang Wijianto; Andhi Fahrurroji; Muhammad Akib Yuswar; Hafrizal Riza (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The impact of the Covid-19 pandemic is felt by the people of Pontianak, in the economic, sociocultural, and health fields. One of the prime commodities in Pontianak is corn farming. The aim of the PKM Program is to innovate corn-based processed products. This PKM activity began with outreach to the heads and employees of the Puskesmas, as well as identifying health cadres as potential participants in training related to using corn silk as herbal tea drinks. Training on using corn silk as herbal tea drinks for cadres was carried out offline and interactively using leaflets, videos, and hands-on practice. Evaluation and monitoring activities are carried out using a Google form (pre-test and post-test). The results of the PKM activity showed success in understanding the cadres with good knowledge when the pre-test was carried out by only ten people (30.30%). After being given knowledge training, respondents in the good category amounted to 30 people (90.90%). PKM activities targeting UPT Puskesmas Perum II cadres increased the ability of cadres to utilize corn silk waste in herbal tea. The next activity is expected to be able to assist so that the resulting product obtains a permit.